Concordance in Reported Love, Trust, and Relationship Quality Among Same-Sex Male Relationships. (21st December 2018) - Bratcher, Anna; Kahle, Erin; Sullivan, Patrick; Hidalgo, Marco A.; Mimiaga, Matthew J.; Garofalo, Rob; Pardee, Dana; Hoehnle, Samuel; Thai, Jennie; Dana, Ruth; Stephenson, Rob
Abstract : This article examines concurrence of self-reported love, trust, and dyadic quality experiences between partners in 293 male couples. Significant yet poor concurrence was observed for all three self-reported relationship measures, but varied by relationship characteristics. Using an actor-partner interdependence model (APIM), actor and partner characteristics were shown to be associated with self-reported relationship concerns, such as satisfaction and intimate partner violence. This knowledge is important in the development and delivery of couples-based health interventions, such as couples HIV testing and counselling, for interventions that respect the unique relationship dynamics of each couple are needed to effectively address dyadic health.